Dynamic changes in species richness and community diversity of symbiotic bacteria in five reproductive morphs of cotton aphid Aphis gossypii Glover (Hemiptera: Aphididae) - Chen, Ruifang; Luo, Junyu; Zhu, Xiangzhen; Wang, Li; Zhang, Kaixin; Li, Dongyang; Gao, Xueke; Niu, Lin; Huangfu, Ningbo; Ma, Xiaoyan; Ji, Jichao; Cui, Jinjie (Frontiers in Microbiology, 2023)
Reproductive polymorphism and symbiotic bacteria are commonly observed in aphids, but their interaction remains largely unclear. In polymorphic aphid species (Aphis gossypii), offspring of parthenogenetic females (PF, G0) develops into sexuparae (G1) which produces gynoparae (G2) and males (G2) successively. Gynoparae (G2) further produces sexual females (SF, G3), and these sexual females mate with males (G2) to produce offspring. In this study, we investigated the dynamic changes of symbiotic bacteria during the above-mentioned 5 reproductive morph switch in A. gossypii via 16S rRNA sequencing technology. The results showed that species richness and community diversity of symbiotic bacteria in males were the highest. Proteobacteria was absolutely dominant bacterial phylum (with relative abundance of more than 90%) in the 5 reproductive morphs of A. gossypii, and Buchnera was absolutely dominant genus (with relative abundance of >90%), followed by Rhodococcus, Pseudomonas, and Pantoea. Male-killing symbiont Arsenophonus presented the highest relative abundance in gynoparae, a specific morph whose offsprings were exclusively sexual females. Both principal component analysis (PCA) and clustering analysis showed trans-generation similarity in microbial community structure between sexuparae (G1) and sexual females (G3), between parthenogenetic females (G0) and gynoparae (G2). PICRUSt 2 analysis showed that symbiotic bacteria in the 5 reproductive morphs were mainly enriched in metabolic pathways. Reproductive morph switch induced by environmental changes might be associated with bacterial community variation and sexual polymorphism of aphids. This study provides a new perspective for further deciphering the interactions between microbes and reproductive polymorphism in host aphids.